A COMPARATIVE STUDY OF CHARACTER PORTRAYAL, SOCIAL AND MORAL VALUES, AND ARTISTIC EXPRESSION IN THE WORKS OF ALISHER NAVOI AND WILLIAM SHAKESPEARE (Ideal Journal of Multidisciplinary Research, 2026)
This article explores the artistic representation of character portrayal, social and moral values, and aesthetic expression in the works of Alisher Navoi and William Shakespeare through a comparative literary perspective. Both authors occupy a central position in their respective literary traditions and have significantly influenced the development of world literature. The study examines how these writers portray human character and ethical values within distinct cultural and historical contexts. Employing comparative-typological analysis and textual interpretation, the research investigates similarities and differences in narrative techniques, thematic structures, and artistic methods used by the two authors. The findings reveal that while both writers address universal human concerns such as morality, justice, love, and social responsibility, their artistic interpretations reflect the philosophical paradigms of their societies. Navoi’s works emphasize spiritual harmony, moral perfection, and ethical guidance rooted in Eastern philosophical traditions, whereas Shakespeare’s dramatic works portray psychological complexity and social tension characteristic of Renaissance humanism. The study contributes to comparative literary scholarship by highlighting the intercultural dialogue between Eastern and Western literary traditions and by demonstrating how character portrayal and ethical values function as universal elements of artistic expression.
Keywords: Comparative literature, character portrayal, social values, moral values, artistic expression, Eastern literature, Renaissance literature, humanism.